Reduced Graphene Oxide-Nanocellulose composite development for supercapacitor application - Zou, Yu (My University, 2024)
The energy problem requires new technologies that move away from non-renewable fossil energy sources. Because of these needs, new energy storage technologies should also be improved. New technologies should not only eliminate fossil energy sources but also utilize solar, wind, or wave energy. Therefore, supercapacitors are a good tool for energy storage. Reduced graphene oxide (rGO) is one of the best ideal materials for supercapacitors. On the other hand, cellulose, the most abundant natural polymer, also needs attention for its effective utilization and value addition by material chemists. Cellulose nanofibers (CNF) can be composed with rGO to make thin films with huge bulk capacitance. CNF can improve the mechanical properties and facilitate the formation of rGO-based thin films as it helps to securely fix the rGO particles without losing their electrical conductivity. The results show that the quality of the films depends not only on the ratio of rGO to cellulose but also on the quality of the rGO formed during the reduction. The mechanistic properties of the film were significantly enhanced when cellulose was mixed with rGO dispersions. The basis of this study was to find the periods for good reduction of GO (30 min, 1 h, 2 h, 3 h, and 6 h, respectively) and to test the electrical conductivity of rGO, rGO: CNF composites at different ratios.